Research on Enterprise Product Strategy Marketing in the Era of the Digital Economy—Taking Huawei Mobile Phones as an Example - Guo, Yiyi (Transactions on Economics, Business and Management Research, 2024)
In the digital intelligence economy era, enterprises' marketing model tend to be precise and refined. As the forerunner and leader of 5G mobile phones, Huawei mobile phones have both risks and opportunities in the era of the digital economy. On the one hand, Huawei’s traditional marketing strategies for mobile phones need to be adjusted and improved. On the other hand, the development of the digital economy has broadened Huawei’s market development space of mobile phones. This study focuses on Huawei smartphones as the primary subject of investigation, meticulously analyzing their marketing strategies within the framework of the SWOT (Strengths, Weaknesses, Opportunities, and Threats) model. It delves into four distinct dimensions: the strengths and weaknesses inherent to Huawei's marketing approach, along with the opportunities and threats it faces in the market. Furthermore, this research proposes concrete strategies for refining Huawei's product marketing tactics, offering valuable insights for enterprises seeking to navigate and thrive in the digital economy era.